Analisis Positioning Merk Laptop dengan Menggunakan Metode MDS Nonmetrik dan CA - Ona Sain, Maria Romaana; Setyawan, Yudi; Bekti, Rokhana Dwi (Jurnal Matematika; Vol 12 No 2 (2022)DO - 10.24843/JMAT.2022.v12.i02.p152, 2023)
Abstract: This study aims to determine the positioning of laptop brands on attributes based on the perceptions and preferences of IST AKPRIND students. The method used is nonmetric multidimensional scaling and correspondence analysis. The results showed that: multidimensional scaling of perception data, quadrant I was occupied by HP and Dell, quadrant II was occupied by Toshiba, quadrant III was occupied by Acer, Lenovo, Asus, and quadrant IV was occupied by Apple. Then multidimensional scaling preference data, it is known that quadrant I is occupied by storage and price attributes, quadrant II is occupied by Apple with attributes of laptop resistance to damage, feature set, RAM, processor, quadrant III is occupied by brand image and warranty attributes, and quadrant IV is occupied by HP, Dell, Toshiba, Acer, Lenovo, Asus, and there are no attributes in quadrant IV. Using correspondence analysis, it is known that quadrant I is occupied by Apple with price attributes, quadrant II is occupied by Toshiba with attributes of brand image, processor, RAM, feature set, quadrant III is occupied by HP, Dell, Lenovo, Acer, Asus with attributes of laptop resistance to damage, quadrant IV is occupied storage and warranty attributes. There is no laptop in quadrant IV.